The Effect of Production and Sales Costs on Financial Performance: Study at One Agroindustry Company in Medan City - Siswanto Siswanto; Cindy Fatika Sari (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Production costs incurred to process raw materials into finished products ready for sale. Sales are revenue transactions in the form of goods or services sent by customers to get cash to appreciate the obligation to pay. This study aimed to determine the effect of production and sales costs on an agro-industrial company in Medan City. This study uses a quantitative method, which uses data from the income statement and cost of goods sold from 2017 to 2019. This research uses primary data sources and secondary data. Primary data comes from the original or first source, and secondary data is already available so that it can search and collect data. Researchers obtained data which were then analyzed using the classical assumption test, normality test, multicollinearity test, autocorrelation test, multiple linear regression, partial test, simultaneous test, and R-square test of the coefficient of determination. The results of the study concluded that the value of production costs count> ttable (-3.859 > 2.03452) and sig <0.05 (0.01 <0.05), so production costs have a negative and significant effect on financial performance. Then H0 is accepted, and Ha is rejected. For sales, t count > t table (2.146 > 2.03452) and sig < 0.05 (0.01 <0.05), it can be concluded that sales have a positive and significant effect on financial performance. Then H0 is accepted Ha is rejected.